Factors of Employee Engagement in Czech Automotive Companies - Drahotsky, Ondrej; Kovacova, Petra; Belas Jr., Jaroslav; Habanik, Jozef (Transformations In Business & Economics, 2025)
This article examines the factors influencing employee engagement in the automotive industry in the Czech Republic. Employee engagement is a critical factor for the success of organisations, as it positively impacts productivity, work quality, and ultimately customer satisfaction. The aim of this research is to define the most significant factors of employee engagement and quantify their importance for both managers and non-managerial staff. The research methodology includes a survey conducted among 442 employees in the Czech automotive industry. The research aims to verify the influence of various factors such as financial rewards, non-financial incentives, company support, tools for achieving work-life balance, quality of the work environment, work relationships, and decision-making authority on the level of employee engagement. The collected data were analysed using a Likert scale and processed through quantitative statistical methods. For managers, the most important factors of employee engagement include salary, decision-making power, opportunity to express an opinion, responsibility, and share of company profit. Non-managerial employees prefer the following engagement factors: salary, hybrid work model, opportunity to express an opinion, decision-making power, and share of company profit. The results demonstrate that all defined factors have a positive impact on employee engagement, with financial factors identified as the most significant. Additionally, it is shown that tools for supporting work-life balance, and the quality of the work environment are also key determinants of engagement. The findings can be applied in practice and integrated into human resource management strategies in the automotive industry. From a scientific perspective, this research expands the knowledge in the field of employee management within the automotive industry, where empirical data is relatively scarce. These results not only provide a basis for further research in this area but also offer practical recommendations for managers who seek to increase employee engagement and thereby improve the efficiency of their organisations.